Identifikasi Kandungan Natrium Nitrit Pada Jajanan Ayam Krispi Pedagang Kaki Lima - Harli Frimana; Fajar Nugraha; Hadi Kurniawan (Journal Syifa Sciences and Clinical Research, 2023)
Sodium nitrite is a food additive that is often used as a preservative in processed meats such as crispy chicken, but excessive and continuous use can cause toxic effects on the body. The purpose of this study was to identify sodium nitrite in crispy chicken in Pontianak city with limits determined by the Regulation of the Head of BPOM RI No 36 of 2013. The research method used in this study was descriptive non-experimental, where as many as 5 samples of crispy chicken were samples A, B, C, D, and E sold by several street vendors in Pontianak City were obtained using purposive sampling technique. Identification of sodium nitrite was carried out qualitatively using BaCl2, AgNO3, and Griess reagents. A positive result for the BaCl2  if it contains sodium nitrite will result in no precipitate forming, a positive result for the AgNO3 will produce a white precipitate, while a positive result for the griess reagent will produce a red-purplish color. The results of the qualitative test using BaCl2 and AgNO3 showed that none of the 5 samples tested were positive for sodium nitrite, while the qualitative test using griess reagent showed that out of the 5 samples tested there were 2 samples containing positive sodium nitrite, namely samples A and D, so that it can be concluded that samples A and D contained positive sodium nitrite in crispy chicken sold by several street vendors in Pontianak city